2014
DOI: 10.1088/2041-8205/792/1/l3
|View full text |Cite
|
Sign up to set email alerts
|

GLOBAL NON-SPHERICAL OSCILLATIONS IN THREE-DIMENSIONAL 4π SIMULATIONS OF THE H-Ingestion FLASH

Abstract: We performed 3-D simulations of proton-rich material entrainment into 12 C-rich He-shell flash convection and the subsequent H-ingestion flash that took place in the post-AGB star Sakurai's object. Observations of the transient nature and anomalous abundance features are available to validate our method and assumptions, with the aim to apply them to very low metallicity stars in the future. We include nuclear energy feedback from H burning and cover the full 4π geometry of the shell. Runs on 768 3 and 1536 3 g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
213
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 108 publications
(223 citation statements)
references
References 21 publications
7
213
1
2
Order By: Relevance
“…There are as yet no detailed models of this process for low-metallicity AGB stars, although PIE events have been identified as a a possible physical site (the i-process, Cowan & Rose 1977;Herwig et al 2011). Overshoot leading to PIEs is uncertain, but known to be favoured in AGB stars of mass ∼1 M and [Fe/H] < 2 (Fujimoto et al 1990;Campbell & Lattanzio 2008;Cristallo et al 2009;Lugaro et al 2012) with recent 3D models supporting these results (Stancliffe et al 2011;Herwig et al 2014;Woodward et al 2015). We stress that one-dimensional hydrostatic models of PIE events with artificial proton distributions like those presented here are not expected to describe the ingestion and the mixing correctly, and this may have a strong effect on the resulting abundance patterns.…”
Section: Discussionmentioning
confidence: 88%
“…There are as yet no detailed models of this process for low-metallicity AGB stars, although PIE events have been identified as a a possible physical site (the i-process, Cowan & Rose 1977;Herwig et al 2011). Overshoot leading to PIEs is uncertain, but known to be favoured in AGB stars of mass ∼1 M and [Fe/H] < 2 (Fujimoto et al 1990;Campbell & Lattanzio 2008;Cristallo et al 2009;Lugaro et al 2012) with recent 3D models supporting these results (Stancliffe et al 2011;Herwig et al 2014;Woodward et al 2015). We stress that one-dimensional hydrostatic models of PIE events with artificial proton distributions like those presented here are not expected to describe the ingestion and the mixing correctly, and this may have a strong effect on the resulting abundance patterns.…”
Section: Discussionmentioning
confidence: 88%
“…If it is confirmed in 3D simulations that no Global Oscillation of Shell H-ingestion (GOSH, Herwig et al 2014) is found in this situation, 1D spherically symmetric simulations of the i-process nucleosynthesis in RAWDs are probably more realistic compared to the case of post-AGB VLTP models and low-Z AGB models for which 3D stellar hydrodynamics simulations have yet to determine the detailed outcome of the GOSH. At a later time (t = 174.8yr) the H-ingestion rate does increase for a brief period when the convection zone is indeed split.…”
Section: The I Processmentioning
confidence: 97%
“…1), and the burning of H creates a split in the He-shell, similar to Herwig et al (2011). 3D simulations are only starting to investigate this process with the necessary numerical effort (Herwig et al 2014), but already show that violent, global instabilities are possible. The 3D behaviour is expected to be fundamentally different compared to what is seen in 1D stellar evolution models.…”
Section: D Stellar Evolution Modelmentioning
confidence: 98%